2014
DOI: 10.1007/s00198-014-2676-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone turnover in diabetes patients—a meta-analysis, and a methodological study on the effects of glucose on bone markers

Abstract: The dissociative pattern of biochemical bone markers of bone formation and bone resorption present in diabetes patients is thus not caused by glucose per se but may be modulated by unknown factors associated with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(127 citation statements)
references
References 42 publications
9
107
1
6
Order By: Relevance
“…However, it is hard to explain how individuals with T2DM can exhibit high porosity [14][15][16][17], since increased cortical porosity reflects increased bone turnover from intracortical surfaces lining the Haversian canals and the endocortical surfaces adjacent to the marrow cavity [18,19]. As T2DM is a condition with low bone turnover [20,21], patients with T2DM would rather be expected to exhibit reduced cortical porosity. In contrast, prior studies reported increased porosity in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is hard to explain how individuals with T2DM can exhibit high porosity [14][15][16][17], since increased cortical porosity reflects increased bone turnover from intracortical surfaces lining the Haversian canals and the endocortical surfaces adjacent to the marrow cavity [18,19]. As T2DM is a condition with low bone turnover [20,21], patients with T2DM would rather be expected to exhibit reduced cortical porosity. In contrast, prior studies reported increased porosity in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bone turnover markers studies in diabetes have had some conflicting results, but the most consistent finding is that markers of resorption (C-terminal cross-linking telopeptide of type I collagen (CTX), N-terminal cross-linking telopeptide of type I collagen (NTX)) and formation (procollagen type I N propeptide (P1NP), osteocalcin) are reduced [47,48]. Methodological studies have excluded a direct effect of glucose in the measurements [48], so the bone turnover markers probably do reflect a true biological effect.…”
Section: Mechanisms Of Action Of T2dm On Bonementioning
confidence: 99%
“…Methodological studies have excluded a direct effect of glucose in the measurements [48], so the bone turnover markers probably do reflect a true biological effect. Histomorphometry in T2D shows decrease in bone volume, osteoid volume, thickness and osteoblast surface, and poor uptake of label indicating reduced bone formation [49,50] consistent with lower turnover from biochemical markers.…”
Section: Mechanisms Of Action Of T2dm On Bonementioning
confidence: 99%
“…However, moving from the preclinical to the clinical setting has been more difficult in establishing the relationship between this system and metabolic homeostasis. (23,53,54) Bioenergetics of the skeleton More recently, attention has focused on other mechanisms related to stem cell fate; in particular, the metabolic program of MSC progenitors. There is now emerging evidence that adipocytes and osteoblasts have distinct energy utilization pathways as they move down their respective lineages during differentiation.…”
Section: Skeletal Control Of Metabolic Balancementioning
confidence: 99%
“…(21) For example, insulin-resistant obese and T2D patients generally exhibit lower bone turnover than nondiabetic normal subjects, as measured by histomorphometry and serum bone turnover markers. (22)(23)(24) In particular, those with previous vertebral fractures have been shown to have higher sclerostin and lower serum IGF-I and PTH levels consistent with reduced bone formation and lower bone turnover. (25,26) Whether this reflects the insulin-resistant state of the individual and hence impairment in the fast-forward cycle, or another process, remains to be determined.…”
mentioning
confidence: 99%